Urban Water Pipe Networks Management Towards Non‐Revenue Water Reduction: Two Case Studies from Greece and Turkey. Issue 7 (6th November 2013) - Kanakoudis, Vasilis; Muhammetoglu, Habib
<x xml:space="preserve">Abstract</x> Non‐revenue water (NRW) accounts for water, revenues, and energy losses. NRW is a big part of the water input in the water distribution systems worldwide, exceeding even 50% in several cases around the globe. The need for conservative water use is today more pressing than ever due to the stressing climate change impacts, forcing water utilities to consider applying effective NRW reduction strategies. The problem gets even worse across the Mediterranean basin that faces severe water scarcity conditions along with increasing water needs. An integrated methodology addressing the NRW problem is currently lacking. The assessment of a network's current operating status based on the International Water Association water balance and performance indicators available is a good start. The real or physical losses represent the biggest "water use" due to the high leakage often being the case. The most effective way to address them is through pressure management. To increase its efficiency, the use of the system's hydraulic simulation model is necessary. The present paper presents two cases (Kos Town in Greece and Antalya City in Turkey) where the above mentioned concept was applied.